The communication strategies for moderate Islamic da’wah in countering radicalism in Gorontalo City, Indonesia - Thaib, Erwin Jusuf (Penerbit Universiti Kebangsaan Malaysia, 2020)
This study focuses on moderate Islamic da’wah communication strategies in counteracting radicalism in Gorontalo City. In Indonesia, radicalism has continuously occurred in the form of suicide bombings leading to lots of life, properties and numerous environmental hazards. Using da’wah as a communication strategy to counteract this violent act by spreading Islamic understanding may affect the community’s attitude. The location was chosen because, besides being the centre for preaching activities, it also has greater social and religious dynamics than the other cities in the province. Meanwhile, the problems in this research are focused on two aspects, which are the content and methods of the moderate Islamic da’wah communication applied by the preachers to counteract radicalism in Gorontalo City. Data were purposively collected from eight preachers through interviews, observations, and documents. The result showed that these strategies were focused on the content of da’wah communication, especially the message and use of the verses. Also, several strategies were utilized by the preachers, which included shaping the community’s religious understanding and reaffirming the position of Muslims as ummatan wasathan. Other strategies were seeking moderate religious references, examining the noble values of Gorontalo culture and customs, and encouraging people to respect and accept diversity.